LATS (Language Assessment Training System) a b-learning proposal for the adquisition of clinical desicion making competences in speech and language intervention - Calleja Reina, Marina (2019)
We described the b-learning tool LATS (Language Assessment Training System) designed from the University of Málaga for training decision making competences for clinical diagnosis in Health Sciences. The LATS is an students online traininig tool to solve virtual simulated caseloads along the decisión making process. The profesor train face to face the decision making process. Our aim is to show the LATS usefulness to improve clinical diagnostic reasoning in 3rd degree students of Speech and Language Faculty in the University of Málaga. Our results shows that students improved their performance using LATS and they appreciated the tool for their learning process.